Altered Functional Magnetic Resonance Imaging Responses to Nonpainful Sensory Stimulation in Fibromyalgia Patients. Issue 11 (November 2014) - López‐Solà, Marina; Pujol, Jesus; Wager, Tor D.; Garcia‐Fontanals, Alba; Blanco‐Hinojo, Laura; Garcia‐Blanco, Susana; Poca‐Dias, Violant; Harrison, Ben J.; Contreras‐Rodríguez, Oren; Monfort, Jordi; Garcia‐Fructuoso, Ferran; Deus, Joan
<x xml:space="preserve">Abstract</x> Objective Fibromyalgia (FM) is a disorder characterized by chronic pain and enhanced responses to acute noxious events. However, the sensory systems affected in FM may extend beyond pain itself, as FM patients show reduced tolerance to non‐nociceptive sensory stimulation. Characterizing the neural substrates of multisensory hypersensitivity in FM may thus provide important clues about the underlying pathophysiology of the disorder. The aim of this study was to characterize brain responses to non‐nociceptive sensory stimulation in FM patients and their relationship to subjective sensory sensitivity and clinical pain severity. Methods Functional magnetic resonance imaging (MRI) was used to assess brain response to auditory, visual, and tactile motor stimulation in 35 women with FM and 25 matched controls. Correlation and mediation analyses were performed to establish the relationship between brain responses and 3 types of outcomes: subjective hypersensitivity to daily sensory stimulation, spontaneous pain, and functional disability. Results Patients reported increased subjective sensitivity (increased unpleasantness) in response to multisensory stimulation in daily life. Functional MRI revealed that patients showed reduced task‐evoked activation in primary/secondary visual and auditory areas and augmented responses in the insula and anterior lingual gyrus. Reduced responses in visual and auditory areas were correlated with subjective sensory hypersensitivity and clinical severity measures. Conclusion FM patients showed strong attenuation of brain responses to nonpainful events in early sensory cortices, accompanied by an amplified response at later stages of sensory integration in the insula. These abnormalities are associated with core FM symptoms, suggesting that they may be part of the pathophysiology of the disease.